The Moderating Role of Gender in Exploring Impulse Buying Behavior Among Gen Z in Live Streaming Shopping: A Stimulus-Organism-Response (SOR) Perspective - Mario, Andre Sandrianus; Vidyanata, Deandra (Universitas Brawijaya, Indonesia, 2025)
The accelerating development of digital platforms has led to a reshaped consumer behavior, especially in live streaming shopping, which combines interactivity, playfulness, and convenience to drive unplanned purchases. Despite growing interest in this phenomenon, limited studies have examined how playfulness interacts with other stimuli to shape impulse buying intention, especially among Generation Z, the dominant users of TikTok. This study focused on the relationships among convenience, interactivity, and playfulness and impulse buying intention, with perceived enjoyment functioning as a mediating variable within the Stimulus–Organism–Response (SOR) framework and gender as a moderating variable, using non-probability purposive sampling. The population consisted of Indonesian Generation Z who actively use TikTok Live Shopping, and 353 respondents were surveyed online in accordance with recommended sampling criteria. This study collected data via an online questionnaire measuring all constructs using a 5-point Likert scale and was analyzed using Smart PLS with the SEM-PLS technique. Additionally, perceived enjoyment acts as a mediator between the three stimulus variables towards impulse buying intention, while convenience, interactivity, and playfulness also exert direct effects. These results highlight playfulness as the strongest determinant in creating enjoyable experiences that foster impulsive behavior. Gender was found to moderate only the relationship between playfulness and impulse-buying intention, suggesting that the entertainment aspect affects men and women differently. Theoretically, this study advances the application of the SOR model in digital commerce by highlighting perceived enjoyment as a key mediating mechanism. Practically, it provides actionable implications for marketers to enhance the TikTok live shopping experience by ensuring seamless convenience, fostering interactive communication, and incorporating playful elements that appeal to Generation Z consumers.